METAFISIKA MASA KINI: Suatu Ulasan atas Metafisika Herman Berger - Snijders, Adelbert (UNIKA Santo Thomas, 2005)
The metaphysics of Herman Berger (1924 - ) may be called TranscendentalÂ Thomism. Berger himself calls his metaphysics, Hermeneutics. The originalÂ text of the metaphysics of Thomas Aquinas is ambiguous. The intuition ofÂ Thomas is a metaphysics of being. The relation between beings and essence isÂ a relation between act (of being) and potency. Being is prior to the essence.Â But in the beginning the metaphysics of Thomas seems to be a metaphysics ofÂ essences. The ground of uniqueness is not being but the essence. In theÂ theory of representationism the startingpoint is a dualism of immanence andÂ transendence. As long as the startingpoint is a kind of dualism, there is no wayÂ to know the correspondence between knowledge (immanent) and the realityÂ outside (transcendent). The transcendental method asks â€œwhat kind of (pre)-Â knowledge makes me aware that my knowledge is finiteâ€. That is onlyÂ possible by the presence of an infinite knowledge. Our knowledge is at theÂ same time infinite and finite, immanent and transcendent, divine and human.Â The first is pre-nowledge; complete but implicit, vague and needs to beÂ expressed conceptually. The latter is explicit but never complete. Anexplicitation is true in so far it expresses the implicit knowledge. A concept is clear but never complete because it is universal, while reality is concrete andÂ individual. The pre-knowledge is â€œas wide as all the realityâ€; it is the groundÂ for judging whether an explanation is true or not. All beings have a verticalÂ relation to Being because they are contingens. Every uniqueness is a gift.Â There are degrees of uniqueness and everything has its own individualityÂ according to its being.